Aggregate Production Functions: Some CES Experiments - Fisher, Franklin M.; Solow, Robert M.; Kearl, James M. (Review of Economic Studies, 1977)
Franklin M. Fisher, Robert M. Solow, James M. Kearl; Aggregate Production Functions: Some CES Experiments, The Review of Economic Studies, Volume 44, Issue